Laparoscopic management of neonatal ovarian cysts - Oak Sanjay; Parelkar S; Akhtar T; Pathak R; Vishwanath N; Satish K; Kiran R (Journal of Indian Association of Pediatric Surgeons, 2005)
The first prenatal detection of an ovarian cyst was by Valenti in 1975. Since then antenatal and neonatal ovarian cysts are encountered more frequently due to the improvement of imaging techniques as well as routine antenatal ultrasound scanning. We discuss here the laparoscopic management of three cases of neonatal ovarian cysts. This approach is well tolerated by neonates, and it may overcome the controversy between the ′wait and see′ policy and early surgical intervention, as laparoscopy has both diagnostic and therapeutic value with minimal morbidity, and ovarian salvage whenever possible.